A pure zinc membrane with degradability and osteogenesis promotion for guided bone regeneration: In vitro and in vivo studies. (1st April 2020) - Guo, Hui; Xia, Dandan; Zheng, Yufeng; Zhu, Yuan; Liu, Yunsong; Zhou, Yongsheng
ABSTRACT: Selection of an appropriate membrane material for guided bone regeneration (GBR) is still ongoing among resorbable and nonresorbable membranes with different characteristics. The major problem with nonresorbable membranes is the inevitable secondary surgery, while resorbable polymer membranes have limitations in providing sufficient mechanical support during the bone repair period due to premature loss of mechanical strength. Pure magnesium foil has been evaluated to explore its feasibility as a resorbable GBR membrane. It exhibited better mechanical properties, whereas poor formability and fast degradation rate were noted. In light of this, pure zinc membrane was developed as a pilot research in this paper. We designed three types of pure zinc membranes: pure Zn without pores, pure Zn with 300 µm diameter and 1000 µm diameter pores, and pure titanium without pores as a control. The mechanical property, in vitro immersion tests, and MC3T3-E1 cell viability assays were tested. Moreover, in vivo behaviors of three type zinc membranes were evaluated by using a rat calvarial critical-sized bone defect model. The experimental results indicated that pure Zn membrane with 300 µm pores showed the most favorable osteogenic capability, comparable to that of titanium membrane without pores. Therefore, considering appropriate degradation rate, adequate mechanical maintenance, and profitable osteogenic capacity, metallic pure zinc is believed to be a promising candidate for barrier membranes in GBR therapy for bone regeneration, and its mechanical property can be enhanced with further alloying. Statement of Significance: Metallic element zinc plays a pivotal role in the growth and mineralization of bone tissues. As a pilot research, three type of guided bone regeneration (GBR) membranes were developed in the present work: pure Zn without pores, pure Zn with 300 µm-diameter and 1000 µm-diameter pores respectively. The mechanical property, in vitro immersion tests and MC3T3-E1 cell viability assays were tested, with pure titanium without pores as a control, thereafter the in vivo performance were evaluated by using a rat calvarial critical-sized bone defect model. It indicated that pure Zn membrane with 300 µm pores showed the most favorable osteogenic capability, comparable to that of titanium membrane control, and is believed to be a promising material candidate as barrier membrane in GBR therapy for bone regeneration. Graphical abstract: Image, graphical abstract